Ketidakseimbangan Th17 dan Treg Pada Pasien PCOS Dengan Resistensi Insulin: Tinjauan Literatur Terhadap Potensi Suntikan Terapi - Franciska, Shelly; Hestiantro, Andon; Kartika, Tasya (Jurnal Kedokteran Universitas Palangka Raya, 2025)
Polycystic ovary syndrome or polycystic ovary syndrome (PCOS) is a metabolic-endocrine disorder characterized by oligoovulation/anovulation, hyperandrogenism, and polycystic ovaries on ultrasound. Globally, PCOS affects 6-21% of women of reproductive age and about 95% of them experience insulin resistance. In Indonesia, the prevalence of PCOS reaches 5-10% where 72.04% are associated with infertility and insulin resistance. Immunoendocrinology notes that the immune response plays a role in the development of PCOS. Several mechanisms cause chronic inflammation caused by insulin resistance, hyperandrogenemia, and dyslipidemia. Research shows a correlation between pro-inflammatory cytokines, especially T-helper 17 (Th17) cells and T-regulatory cells (Treg), in PCOS and insulin resistance. Th17 cells increase inflammation, while Tregs play the opposite role, with their differentiation modulated by interleukin-6 (IL-6) and Transforming Growth Factor-β (TGF-β). Th17/Treg balance can be regulated by targeting IL-6. This study compared Th17 and Treg levels in PCOS patients with and without insulin resistance using IL-17 and IL-10 markers. Th17 was higher and Treg was lower in PCOS with insulin resistance, resulting in a higher Th17/Treg ratio compared to patients without insulin resistance. The results of this study provide an opportunity to target the Th17/Treg axis in new therapies to break the cycle of PCOS and insulin resistance and reduce complications